The Effects of Privacy Awareness, Security Concerns and Trust on Information Sharing in Social Media among Public University Students in Selangor - Anjuman Ara; Zuraidah Zainol; Duraisamy, Balaganesh (International Business Education Journal, 2022)
The purpose of this research was to investigate the effect privacy awareness as well as security concerns both on trust, privacy awareness, security concerns and further trust on information sharing then privacy awareness only on security concerns on platforms for social networking. A quantaitative approach was used in this research. 500 students from public universities who ranged in age of 18 to 29 were used as a selected sample for the data collection. A questionnaire as an instrument was used to obtain the actual data and the selection of respondents was made using the systematic street-intercept method. To analyse the data, descriptive analysis and covariance-based structural equation modeling (CB-SEM) were employed. Outcomes of the research revealed that privacy awareness (PA) significantly predicts security concerns (SC). A significant predictor of trust is shown to have both PA and SC. However, the effect of PA is positive, while SC is negative. Only PA and trust significantly affect the information sharing (IS), not SC. Trust is more likely to increase the willingness to share information, but the higher the SC, the less likely for the students to share information. In conclusion, to promote IS on social media platforms, trust should be built among the users. Despite that privacy awareness could reduce the willingness to share information, it plays a critical role to build trust. In implication, to win and secure the online users, the online service providers and sellers should overcome the trust and privacy issues.